The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcell.2021.657149
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Regulator Patz1 Is Essential for Neural Stem Cell Maintenance and Proliferation

Abstract: Proper regulation of neurogenesis, the process by which new neurons are generated from neural stem and progenitor cells (NS/PCs), is essential for embryonic brain development and adult brain function. The transcription regulator Patz1 is ubiquitously expressed in early mouse embryos and has a key role in embryonic stem cell maintenance. At later stages, the detection of Patz1 expression mainly in the developing brain suggests a specific involvement of Patz1 in neurogenesis. To address this point, we first got … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…It has been suggested that hippocampus damage plays a vital role in the pathophysiology of epilepsy and depression. [ 35 ] In the present study, H&E analysis indicated a neuronal loss in the hippocampal regions (CA1, CA3, and CA1) of PTZ mice. Meanwhile, remarkably increased FJB‐positive cells, which represent neuronal degeneration, were also exhibited in PTZ group, while administration of EPA produced the best effect on the significant reduction of the degeneration of the hippocampus.…”
Section: Discussionsupporting
confidence: 58%
“…It has been suggested that hippocampus damage plays a vital role in the pathophysiology of epilepsy and depression. [ 35 ] In the present study, H&E analysis indicated a neuronal loss in the hippocampal regions (CA1, CA3, and CA1) of PTZ mice. Meanwhile, remarkably increased FJB‐positive cells, which represent neuronal degeneration, were also exhibited in PTZ group, while administration of EPA produced the best effect on the significant reduction of the degeneration of the hippocampus.…”
Section: Discussionsupporting
confidence: 58%
“…Next, we sought to identify TFs with differential activity associated with chromatin accessibility by motif footprinting using HINT-ATAC and motif enrichment with GimmeMotifs maelstrom. HINT analysis using the CIS-BP motif database identi ed decreased footprinting activity of TFs controlling neuron differentiation (HEYL, PATZ1) [91,92], mitochondrial energy and neuron function (NRF1, GMEB1) [93], as well as synaptic plasticity (CREM) [94] and increased footprinting activity of early pro-neural TFs (ASCL1, NEUROG2, ARNT2) [95,96] across all three mutations (Fig. 3D-F).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, PATZ1 overexpression in LUSCs appears consonant with the stem cell phenotype of this subtype. In fact, PATZ1 is required for pluripotency maintenance of embryonic stem cells [ 51 ], plays an essential role in the reprogramming of differentiated cells toward stem cells [ 13 ], and governs the self-renewal ability of adult stem cells, including neural and cancer stem cells [ 52 , 53 ]. Strikingly, the expression of PATZ1 and the stem cell marker SOX2 are positively associated in NSCLC tissues ( Figure S8 ).…”
Section: Discussionmentioning
confidence: 99%